Konsep diri dan kecenderungan melakukan agresivitas verbal pada remaja pengguna media sosial - Mughni Alif Al Rosyad; Sahat Saragih; Eko April Ariyanto (INNER: Journal of Psychological Research, 2022)
Abstract This study aims to determine empirically the relationship between self-concept and the tendency to engage in verbal aggression on adolescent social media users. The analysis of this study used independent variables, namely self-concept and verbal aggression variables. The sample in this study were teenagers using social media. This study used the incidental sampling method by distributing the self-concept scale and the scale of verbal aggression online to 119 research subjects based on predetermined criteria. The statistical method used is the Spearman Brown correlation test. The results of this study indicate that the value of rxy = -0.501 with P <0.05 indicates that self-concept contributes to the tendency to engage in verbal aggression by 25%. Apart from self-concept, there are other variables or factors that influence verbal aggression, such as emotional regulation, self-control, religions, and so on. So it can be concluded that there is a negative relationship between self-concept and verbal aggression, in other words the more positive the level of self-concept, the lower / negative the level of verbal aggression. Vice versa, the lower the level of self-concept, the higher the level of verbal aggression. Keywords: Self-Concept, Verbal Aggression, Adolescent, Social Media